Tracking Access to Nonsolid Fuel for Cooking - Ghosh Banerjee, Sudeshna (World Bank, Washington, DC, 2014)
The World Health Organization estimates that in 2012 about 4.3 million deaths occurred because of exposure to household air pollution caused by smoke from the incomplete combustion of fuels such as wood, coal, and kerosene. Inefficient energy use in the home also poses substantial risks to safety, causing burns and injuries across the developing world. To support the achievement of these goals, a starting point must be set, indicators developed, and a framework established to track those indicators until 2030. The World Bank and International Energy Agency have led a consortium of 15 international agencies to produce data on access to nonsolid fuel for the SE4ALL Global Tracking Framework. Launched in 2013, the framework defines access to modern cooking solutions is as the use of nonsolid fuels for the primary method of cooking. Nonsolid fuels include (i) liquid fuels (for example, kerosene, ethanol, or other biofuels), (ii) gaseous fuels (such as natural gas, LPG, and biogas), and (iii) electricity. These are in contrast to solid fuels such as (i) traditional biomass (wood, charcoal, agricultural residues, and dung), (ii) processed biomass (pellets, briquettes); and (iii) other solid fuels (such as coal and lignite).